Управление инвестиционной привлекательностью аграрного сектора - Плотникова, М.Ф.; Присяжнюк, О.Ф. (Культура народов Причерноморья, 2013)
В статті розглянуті теоретично-методологічні підходи до оцінки й управління інвестиційною привабливістю. Запропоновані підходи до систематизації й класифікації факторів й критеріїв інвестиційної привабливості суб’єктів господарювання в Україні. розглянуті базові моделі взаємодії інвесторів й об’єктів інвестиційної діяльності з позицій управління обсягами виробництва й факторами, які їх визначають. В статье рассмотрены теоретико-методологические подходы к оценке и управлению инвестиционной привлекательностью. Предложены подходы к систематизации и классификации факторов и критериев инвестиционной привлекательности субъектов хозяйствования в Украине. Рассмотрены базовые модели взаимодействия инвесторов и объектов инвестиционной деятельности с позиций управления объемами производства и факторами, которые их определяют. Theoretical and methodological approaches to investment attractiveness evaluation and management were considered at the article. Approaches to systematization and classification of investment attractiveness factors and criterions of business entities in Ukraine according to assessment forms and levels, types, purposes, methods as well as analysis subject priority were suggested. Basic models of investors and investment activity subjects interaction from the position of production volume management and their determinative factors were examined by the authors. Prospects of production volume increasing as in conditions of total absence so in presence of such factor as competition were estimated. Interaction of production and temporal factors was revealed, synergetic effect estimation in the issue of investor and business entity interaction was submitted as analytically so graphically. The article key moment is development and argumentation of investment and innovation product introduction algorithm by active management system in Ukraine agrarian sector analyzing.